Nitrogen Loading Enhances Stress Impact of Drought on a Semi-natural Temperate Grassland - Kübert, Angelika; Götz, Miriam; Kuester, Emma; Piayda, Arndt; Werner, Christiane; Rothfuss, Youri; Dubbert, Maren (Frontiers in Plant Science, 2019)
Two important threats to the sustainable functioning of semi-natural grasslands in temperate zones are 1) nutrient loading due to agricultural fertilization and pollution, and 2) the increase of extreme drought events due to climate change. These threats may cause substantial shifts in species diversity and abundance and considerably affect the carbon and water balance of ecosystems. The synergistic effects between those two threats, however, can be complex and are poorly understood. Here, we experimentally investigated the effects of nitrogen addition and extreme drought (separately and in combination) on a semi-natural temperate grassland, located in Freiburg (South Germany). To study the grassland response, we combined eddy covariance techniques with open gas exchange systems. Open gas exchange chambers were connected to an infrared gas analyzer and water isotope spectrometer, which allowed the partitioning of net ecosystem exchange and evapotranspiration. Vegetation parameters were described by species richness, species abundance and leaf area index. Our results suggest that grassland communities, strongly weakened in their stress response by nitrogen loading, can substantially lose their carbon sink function during drought. While nitrogen addition caused a significant loss in forb species (₋25%), precipitation reduction promoted a strong dominance of grass species at season start. Consequently, the grass dominated and species-poor community suffered from a strong above-ground dieback during the dry summer months, likely caused by lower water use efficiency and weaker drought adaptations of the species community. Over the growing season (April-September) the carbon sequestration of the studied grassland was reduced by more than 60 % as a consequence of nitrogen addition. Nitrogen addition in combination with precipitation reduction decreased carbon sequestration by 73 %. Eutrophication can severely threaten the resilient functioning of grasslands, in particular when drought periods will increase as predicted by future climate scenarios. Our findings emphasize the importance of preserving high diversity of grasslands to strengthen their resistance against extreme events such as droughts.